Opportunities at Higher Education Institutes in India: Small Cases on Enhancing Skills (International Journal of Innovative Research in Computer Science & Technology, 2020)
This article basically tries to explain that  opportunities are the key to success and how students can  take advantage and learn new skills or to enhance existing  ones. it is an understanding of the opportunities and using  the strengths in the right way which in turn helps in  achieving better. Higher education institutes provide  platform to every individual, and can seek opportunities not  just by looking at what he/she can do but rather he/she must  be built in such way that they can recognise or analyse how  he/she can use the resources or qualities that they already  have within them or may build. This article is based on  some case studies done on students of Amity University  Haryana, India. And found how their personality changed  during their degree at institute in terms of enhancing skills  through opportunities. These students are always very  positive in approach and were keen to learn and do  something better for country.
Keywords: Opportunities; positive; Strengths; and weaknesses; skills